Land use changes: The initiator of environmental problem - Mariyappan, Raman; Perumal, Selvan (2004)
The aim of this paper is to point out the influence of land use changes on environmental tragedies, and also to show how sudden shift in land use pattern due to economic development can contribute towards environmental degradation. Changes in land usage and land use pattern, mostly considered the most affecting factor involving environmental disaster tragedies. The current threat to the environment, which is a common concern of all mankind, stems essentially fiom past neglect in managing the natural environment and resources. In the developed world, especially in Europe, agriculture has caused the removal of a significant proportion of the natural vegetation. The most, significant impacts of agriculture in the developing world are deforestation, desertification, salnisation and soil erosion. In just a few decades, major parts of Asia have transformed fioin essentially traditional agricultural societies to intensive export oriented industrial economics, plunging the region into severe ecological and social disruption. Environmental change is a continual process that has been in operation since the earth first came into existence some 5,000,000,000 years ago. The change occurred drastically when man made powerful change through his capacity to develop technology. This can occur directly through activities such as habitat loss and urban expansion. Malaysia, which experiences a unique situation where the significant economic development was achieved without sacrificing most of the natural environment. However, the recent shift in the economic sector has created a new fear, the present balance between economic development and natural environment can not be sustained